Evaluation of the IVF success in frozen-thaw in vitro fertilization cycles in terms of endometrial thickness - Mustafa Bertan Demir; Davut Guven; Ilhami Ersoy (Medicine Science, 2023)
The aim of this research was to analyze the link between endometrial thickness (EMT), as measured during progesterone administration, and the results observed in individuals who underwent frozenthawed embryo transfer. A retrospective analysis was performed on 233 hormone replacement therapy (HRT) methods of endometrial preparation in frozen-thawed embryo transfer (FET) cycles (HRT-FET). HRT-FET cycles that were conducted between January 2021 and December 2022 at the In vitro fertilization (IVF) Clinic of 19 May University Medical Faculty Training and Research Hospital. The patients' age, infertility duration, basal follicle-stimulating hormone (FSH) level, body mass index (BMI), number and day of embryos transferred, and pregnancy rates were evaluated. Endometrial thickness was measured using transvaginal ultrasound (TV USG) on the day of progesterone administration. The endometrial thickness of patients who achieved clinical pregnancy and those who did not were analyzed. No significant differences in demographic factors were found between the groups in terms of age, infertility duration, basal FSH level, and BMI (p=0.209, p=0.959, p=0.866 and p=0.685, respectively) . The success rates of clinical pregnancy did not strongly correlate with endometrial thickness. The study found that EMT is not a valid indicator for clinical pregnancy in frozen-thawed embryo transfer cycles. [Med-Science 2023; 12(4.000): 1306-9]